The Molecular Surface Property Approach: A Guide to Chemical Interactions in Chemistry, Medicine, and Material Science. Issue 1 (25th November 2018) - Brinck, Tore; Stenlid, Joakim H.
Abstract: The current status of the molecular surface property approach (MSPA) and its application for analysis and prediction of intermolecular interactions, including chemical reactivity, are reviewed. The MSPA allows for identification and characterization of all potential interaction sites of a molecule or nanoparticle by the computation of one or more molecular properties on an electronic isodensity surface. A wide range of interactions can be analyzed by three properties, which are well‐defined within Kohn–Sham density functional theory. These are the electrostatic potential, the average local ionization energy, and the local electron attachment energy. The latter two do not only reflect the electrostatic contribution to a chemical interaction, but also the contributions from polarization and charge transfer. It is demonstrated that the MSPA has a high predictive capacity for non‐covalent interactions, for example, hydrogen and halogen bonding, as well as organic substitution and addition reactions. The latter results open up applications within drug design and medicinal chemistry. The application of MSPA has recently been extended to nanoparticles and extended surfaces of metals and metal oxides. In particular, nanostructural effects on the catalytic properties of noble metals are rationalized. The potential for using MSPA in rational design of heterogeneous catalysts is discussed. Abstract : Chemical interactions of molecules, nanoparticles and surfaces are analyzed using the molecular surface property approach. The variations of electrostatic and polarization/charge‐transfer properties on isodensity surfaces of chemical compounds reveal the local propensity to interact with electron donors and acceptors. Site‐specific preferences to participate in electrostatically or charge‐transfer dominated interactions are rationalized, allowing for predictions of both regioselectivity and global reactivity.